Factors contribute to absenteeism of employees in organization / Wan Nursyuhada Wan Jusoh - Wan Jusoh, Wan Nursyuhada (2014)
The study was conducted in order to find out the significant relationship between the independent variables with the dependent variable. The dependent variable is absenteeism of employees in organization. The independent variables in this study are tenure, flexible work hours, and pay. The results of the findings were interpreted using Reliability Test, Frequency Distribution, Descriptive Statistics, and Pearson’s Correlation Coefficient. The population of the study is in CTRM Aero Composites Sdn Bhd referred to 275 employees. From the population, the sample size been selected is 160 employees in Value Stream 4 of non- executive employees which selected employees in Quality Control Department. This study sampling design is using restricted or complex probability sampling which is proportionate stratified random sampling.